34. SOME FACTORS RELATED TO PATIENT CARE RESULTS SPINAL CORD INJURY WITH NERVE BLADDER (Vietnam Journal of Community Medicine, 2024)
Objective: To analyze a number of factors related to the results of care for patients with neurological bladder due to spinal cord injury at the Rehabilitation Center, Bach Mai Hospital in 2022.Subject and method: Cross-sectional description of 133 patients aged 18 years and older, diagnosed with neuromuscular bladder treatment at the Rehabilitation Center, Bach Mai Hospital.Results: The rate of poor care in patients with spinal cord injuries with neurological bladder was 18% and this rate was higher in retired patients compared to other occupations (38.9% compared to 14.8%); patients with upper-secondary school education compared to lower-secondary school (23.8% compared to 9.4%); in patients who have not achieved dietary care compared to patients (38.9% compared to 14.8%) and patients who have not achieved respiratory care compared topatients who achieved respiratory care (41.2% compared to 14.7%). Conclusion: The incidence of poor care in patients with spinal cord injury with neurobladder in the study was 18%. Some factors related to poor care are: patients with qualifications below upper secondary school, patients who have not retired, patients who have not received care in terms of eating and breathing.
Keywords: Neurogenic bladder, related factors, spinal cord damage.